Multiple objective analytics for criminal justice systems - Evans, Gerald W. (Boca Raton : CRC Press, 2021)
"Criminal justice systems are complex and difficult to design and operate. This is due to their many interacting parts, and their dynamic and probabilistic nature, as well as their interfaces with other systems. This book reviews the use of analytics to address issues in criminal justice system and discusses the various sources of data associated with the systems. This book is meant to be used by those who would like 1) an introduction to criminal justice systems and 2) an illustration of how some of the various methodologies of analytics can be used to address specific issues in criminal justice systems. This book will be of interest to faculty, students, and researchers in schools/departments of criminal justice, law, public affairs, political science, industrial engineering, and management. In addition, the book should be of use to government analysts who study the effects of criminal programs and laws"--
OCLC-licensed vendor bibliographic record.
Keywords: Criminal justice, Administration of -- Statistical methods; Multiple criteria decision making; LAW / Criminal Law / General; TECHNOLOGY / Operations Research; BUSINESS & ECONOMICS / Operations Research